Unemployment Compensation Finance and Efficiency Wages - Albrecht, James W.; Vroman, Susan B. (Journal of Labor Economics, 1999)
This article examines the effects of unemployment compensation finance in a labor market in which firms pay efficiency wages. Two self‐financing unemployment compensation systems are compared: one in which benefits are financed by a proportional payroll tax and another in which experience rating is introduced by taxing firms in proportion to their separations. We find that experience rating leads to less unemployment, less shirking, and higher output.